Dividend Yeld: ICG versus IBOV (Revista Brasileira de Contabilidade e Gestão, 2012)
Through the Agency Conflicts, which analyse costs resulting from the ramification between property and capital control, practices of corporate governance appear. Facing it, some institutions started to act with the intention of stimulating good practices and warrant rights to minor stockholders. There are affirmations that the stocks evaluated with the Corporate Governance Ratings (CGR) would have a different distribution in relation to the dividends of the stocks evaluated with the Bovespa Rating (IBOV), being the dividends higher in the companies with good practices of corporate governance. The objective is to verify if the companies compounding the CGR had distributed the dividends differently and if these dividends are higher than those from companies that are components of IBOV. The study is justified for the fact that, nowadays, there are billionaire volumes in daily negotiation in the BMF&Bovespa, environment in which the investment decision must suffer influence from the governance indicators. Theoretical portfolios from 2006 were collected for both ratings. It was used as proxy the weighted average of the dividend yields of each stock having as weighing the relevance of such stocks inside the ratings. A descriptive data analysis was held, followed by a test of averages between the weighing of the dividend yields of the ratings. Higher dividend yields were found for the IBOV. However, the test of averages led to the conclusion that there is no difference between the dividend distributions, demonstrating that the corporate governance practices do not result in better dividend distributions.
Keywords: corporate governance; agency theory; dividen yield